Solving fuzzy differential equation using fourth-order four-stage improved Runge– Kutta method - Rabiei, Faranak; Ismail, Fudziah; Emadi, Saeid (Springer, 2016)
In this paper the fuzzy improved Runge–Kutta method of order four for solving first-order fuzzy differential equations is proposed. The scheme is two step in nature and is based on the fourth-order improved Runge–Kutta method for solving first-order ordinary differential equations. The numerical examples are tested to illustrate the efficiency of method